Inversions on human chromosomes - Kosuthova, Klara; Solc, Roman (American journal of medical genetics. Part A, 2023)
Human chromosome inversions are types of balanced structural variations, making them difficult to analyze. Thanks to PEM (paired-end sequencing and mapping), there has been tremendous progress in studying inversions. Inversions play an important role as an evolutionary factor, contributing to the formation of gonosomes, speciation of chimpanzees and humans, and inv17q21.3 or inv8p23.1 exhibit the features of natural selection. Both inversions have been related to pathogenic phenotype by directly affecting a gene structure (e.g., inv5p15.1q14.1), regulating gene expression (e.g., inv7q21.3q35) and by predisposing to other secondary arrangements (e.g., inv7q11.23). A polymorphism of human inversions is documented by the InvFEST database (a database that stores information about clinical predictions, validations, frequency of inversions, etc.), but only a small fraction of these inversions is validated, and a detailed analysis is complicated by the frequent location of breakpoints within regions of repetitive sequences.
Keywords: lidské chromozomy; lidé; Repetitive Sequences, Nucleic Acid; Chromosome Inversion; Chromosomes; chromozomy; Polymorphism, Genetic; Chromosomes, Human; chromozomální inverze; Evolution, Molecular; molekulární evoluce; polymorfismus genetický; repetitivní sekvence nukleových kyselin; Humans